An examination of the curvilinear relationship between person-job fit and innovative behavior: the moderating role of abusive supervision in South Korea - Kim, Jinhee; Lee, Soojin (Frontiers in Psychology, 2024)
Although literature suggests that a higher person-job fit leads to more innovative behavior, some recent studies have shown inconsistent results with the assumption of such a linear relationship between the two constructs. Considering these inconsistent findings, the present study aims to examine a curvilinear relationship between person-job fit and innovative behavior. Innovative behavior represents an individual's actions that come up with, realize, and apply novel ideas within the job environment, and person-job fit, which pertains to the value congruence between the job and individual, can be a critical predictor of innovative behavior. Drawing on the triphasic model of stress and the conservation of resources theory, this study hypothesizes that person-job fit has a non-linear relationship with innovative behavior, and that abusive supervision moderates this relationship. The regression analysis results of the 180 employee-supervisor dyadic data revealed that person-job fit and innovative behavior have a non-linear relationship. Furthermore, the non-linear relationship is (1) weakened (linearly positive) when abusive supervision is high and (2) strengthened when abusive supervision is low. By integrating multiple theoretical lenses, the present study offers a more sophisticated understanding of individual employees' psychological reactions to job fit discrepancies and their innovative outcomes in organizational settings. Theoretical and practical implications and directions for future research are also discussed.